The influence of biomass Coriolus versicolor on indexes of inmmunoreactivity of organism on experimental model - Антоненко, Лариса Олександрівна; Лазаренко, Людмила Миколаївна; Клечак, Інна Рішардівна (Eastern-European Journal of Enterprise Technologies, 2012)
Immunomodulating properties of the biomass Coriolus versicolor 353 was found in an experimental model in mice in vivo. Preparation of the biomass C.versicolor 353 enhances the ability of macrophages of the abdominal cavity of mice to the accumulation of intact reactogenic metabolites of oxygen and their phagocytic activity